Modelo de infecção gastrintestinal e o papel do LPS, urease e sistema de secreção do tipo 4 da Brucella melitensis em camundongos - Tatiane Alves da Paixao (2009)
Human brucellosis is caused mainly by Brucella melitensis, which is often aquired by ingesting contaminated goat or sheep milk and cheese. Bacterial factors required for oral infection by B. melitensis are poorly understood. In this study, a mouse model of gastrointesinal infection was developed to assess the roles of the urease, type IV secretion system (T4SS), and lipopolysaccharide (LPS) for establishing infection through the digestive tract. Female BALB/c mice were inoculated intragastrically by gavage with 1x1010 CFU of wild type B. melitensis strain 16M or mutant strains. Tissue samples were collected for CFU counting. B. melitensis 16M was consistently recovered from the mesenteric lymph node, spleen, and liver beginning at 3 or 7 dpi. In the gut, a marked decline of CFU numbers was observed up to 21 dpi. No inflammatory lesions were observed in ileum or colon during infection. Mutant strains carrying deletion of the urease subunits protein of the ure1 operon, deletion of virB2, or deletion of pmm were constructed and compared at wild type strain. ure1 mutant was attenuated in the spleen (p<0.05) whereas virB2, and pmm mutants were attenuated in the spleen (p<0.05) and mesenteric lymph node (p<0.001). Wild type and mutant strains had similar resistance to low pH and 5 or 10% bile suggesting that the reduced colonization of mutants was not the result of reduced resistance to acid pH or bile salts. These results indicate that urease, T4SS and LPS are required for wild type infection levels of B. melitensis through the digestive tract